Molecular Analysis of Echinostome Metacercariae from Their Second Intermediate Host Found in a Localised Geographic Region Reveals Genetic Heterogeneity and Possible Cryptic Speciation - Waraporn Noikong (2018)
Echinostome metacercariae are the infective stage for humans and animals. The identification of echinostomes has been based until recently on morphology but molecular techniques using sequences of ribosomal RNA and mitochondrial DNA have indicated major clades within the group. In this study we have used the ITS2 region of ribosomal RNA and the ND1 region of mitochondrial DNA to identify metacercariae from snails collected from eight well-separated sites from an area of 4000 km2in Lamphun Province, Thailand. The derived sequences have been compared to those collected from elsewhere and have been deposited in the nucleotide databases. There were two aims of this study; firstly, to determine the species of echinostome present in an endemic area, and secondly, to assess the intra-specific genetic diversity, as this may be informative with regard to the potential for the development of anthelmintic resistance and with regard to the spread of infection by the definitive hosts. Our results indicate that the most prevalent species are most closely related to E. revolutum, E. trivolvis, E. robustum, E. malayanum and Euparyphium albuferensis. Some sites harbour several species and within a site there could be considerable intra-species genetic diversity. There is no significant geographical structuring within this area. Although the molecular techniques used in this study allowed the assignment of the samples to clades within defined species, however, within these groupings there were significant differences indicating that cryptic speciation may have occurred. The degree of genetic diversity present would suggest the use of targeted regimes designed to minimise the selection of anthelmintic resistance. The apparent lack of geographic structuring is consistent with the transmission of the parasites by the avian hosts. © 2014 Noikong et al.